Measuring ion oscillations at the quantum level with fluorescence light - Cerchiari, G; Araneda Machuca, GA; Podhora, L; Slodička, L; Colombe, Y; Blatt, R (American Physical Society, 2021)
We demonstrate an optical method for detecting the mechanical oscillations of an atom with single-phonon sensitivity. The measurement signal results from the interference between the light scattered by a trapped atomic ion and that of its mirror image. We detect the oscillations of the atom in the Doppler cooling limit and reconstruct average trajectories in phase space. We demonstrate single-phonon sensitivity near the ground state of motion after electronically induced transparency cooling. These results could be applied for motion detection of other light scatterers of fundamental interest, such as trapped nanoparticles.